1998
DOI: 10.1002/(sici)1097-4628(19981107)70:6<1129::aid-app9>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the network structure of hydroxyl terminated poly(butadiene) elastomers prepared by different reactive systems

Abstract: Three types of hydroxyl terminated poly(butadiene) (HTPB) networks having different NCO/OH reactive group ratios were prepared using three different reactive systems (i.e., Desmodur N-100 pluriisocyanate, isophorone diisocyanate (IPDI)/ trimethylol propane (TMP), and hexamethylene diisocyanate (HMDI)/TMP). Desmodur N-100 and TMP were used as polyfunctional reactants. The polymer-solvent interaction parameters ( 1 ) for HTPB-tetrahydrofuran (THF) and HTPB-chloroform systems at 45°C were determined, using a vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 10 publications
4
23
0
Order By: Relevance
“…Swelling testing was performed gravimetrically 8 . Circular discs (10 mm in diameter, 2 mm-thickness, 0.3 to 0.4 g) were previously weighted and placed, in triplicate, into chloroform at room temperature until equilibrium was reached (7 days).…”
Section: Swelling Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Swelling testing was performed gravimetrically 8 . Circular discs (10 mm in diameter, 2 mm-thickness, 0.3 to 0.4 g) were previously weighted and placed, in triplicate, into chloroform at room temperature until equilibrium was reached (7 days).…”
Section: Swelling Testingmentioning
confidence: 99%
“…The swollen sample disks were weighted (w 1 ) and placed to dry up to constant mass (w 2 ). Swelling ratio was calculated by following Equation 1 [8] :…”
Section: Swelling Testingmentioning
confidence: 99%
“…It is synthesized through the ring-opening polymerization of benzoxazine monomer, which is easily prepared from phenols, primary amines and formaldehyde. Wide variation of raw materials allows tremendous flexibility in molecular design and versatile performance as well as the balance between thermal and mechanical performance [1][2][3][4][5][6][7][8][9][10]. The ring-opening polymerization proceeds through thermal treatment without the need of catalyst and without the generation of volatiles, thus maintaining the dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…It is an appropriate choice of modifier for polybenzoxazine, because its low viscosity provides easy handling and the polarity can be adjusted by changing the ratio of polybutadiene and acrylonitrile content. It has been previously reported that the incorporation of reactive liquid rubbers such as amine-terminated poly(butadiene-acrylonitrile) (ATBN) and carboxy-terminated poly(butadiene-acrylonitrile) (CTBN) as modifiers improved toughness [9,10,15], however, glass transition temperature (Tg) of the modified polybenzoxazine was found to decrease with the increasing content of liquid rubber [9]. In this study, we investigated the influence of the terminal groups of ATBN, CTBN and ester-terminated poly(butadieneacrylonitrile) (ETBN) on the ring-opening polymerization of F-a and their compatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used polyol in recent time is the Hydroxyl Terminated Polybutadiene (HTPB). This liquid prepolymer has excellent physical properties such as low glass transition temperature, high tensile and tear strength, and good chemical resistance (Eroglu, 1998). The hydrocarbon nature of HTPB (98.6%) along with low viscosity (5000 mPas at 30 °C) and low specific gravity (0.90 g/cm 3 ), makes it a promising fuel binder for PU propellant.…”
Section: Introductionmentioning
confidence: 99%